Scope of Marketing in Healthcare Sector - Mishra, Sita (Indian Journal of Marketing, 2005)
Today focus on marketing is intensifying in various sectors whether it is consumer, business, international or non profit. More and more organizations in these sectors recognize how marketing can attribute to improve the performance. Marketing is increasingly attracting the interest of non-profit organizations such as educational, healthcare, religious, charity foundations; entertainment etc.The provision of healthcare services is a major constituent of the non-profit sector. With global revenues of approximately US$ 2.8 trillion, the healthcare industry is the world's largest industry and India is emerging as a major player in this industry, because of its high population. India spends over Rs.1,03,000 crore on healthcare, of which delivery market consumes Rs.86,000 crore, while the rest goes to the pharma market. The industry is expected to grow at the rate of 13 percent for the next six years which amounts to an addition of Rs.9000 crores each year.